Aggressive challenging behavior in adults with intellectual disability: An electronic register-based cohort study of clinical outcome and service use - Smith, James; Baksh, R. Asaad; Hassiotis, Angela; Sheehan, Rory; Ke, Chengcheng; Wong, Tsz Lam Bambi; Strydom, André (European psychiatry, 2022)
BackgroundAggressive challenging behavior in people with intellectual disability is a frequent reason for referral to secondary care services and is associated with direct harm, social exclusion, and criminal sanctions. Understanding the factors underlying aggressive challenging behavior and predictors of adverse clinical outcome is important in providing services and developing effective interventions.MethodsThis was a retrospective total-population cohort study using electronic records linked with Hospital Episode Statistics data. Participants were adults with intellectual disability accessing secondary services at a large mental healthcare provider in London, United Kingdom, between 2014 and 2018. An adverse outcome was defined as at least one of the following: admission to a mental health hospital, Mental Health Act assessment, contact with a psychiatric crisis team or attendance at an emergency department.ResultsThere were 1,515 patient episodes related to 1,225 individuals, of which 1,019 episodes were reported as displaying aggressive challenging behavior. Increased episode length, being younger, psychotropic medication use, pervasive developmental disorder (PDD), more mentions of mood instability, agitation, and irritability, more contact with mental health professionals, and more mentions of social and/or home care package in-episode were all associated with increased odds of medium-high levels of aggression. Risk factors for an adverse clinical outcome in those who exhibited aggression included increased episode length, personality disorder, common mental disorder (CMD), more mentions of agitation in-episode, and contact with mental health professionals. PDD predicted better outcome.ConclusionsRoutinely collected data confirm aggressive challenging behavior as a common concern in adults with intellectual disability who are referred for specialist support and highlight factors likely to signal an adverse outcome. Treatment targets may include optimizing management of CMDs and agitation.